Peningkatan Hasil Belajar Peserta Didik Kelas VII 2 SMP Negeri 10 Palembang pada materi Teks Surat dengan Menggunakan Model Problem Based Learning (PBL) - Amrina, Uli; Lestari, Hikmah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Based on the results of pre-research in teaching and learning activities in class and the results of interviews with class VII Indonesian language study teachers at SMP Negeri 10 Palembang, researchers found various problems that emerged as a result of low student learning outcomes, especially writing letters. Several factors cause students to not be able to write personal letters, namely: 1) students still find it difficult to put ideas into letters, 2) the writing of words and content is still not fully expressed, because students are not yet able to optimally put together words. one word with another or one sentence with another sentence, 3) incorrect use of spelling and punctuation. The type of research carried out is Classroom Action Research (PTK). The research procedure carried out refers to the research design proposed by Kemmis and Mc Taggart, namely a cyclical form and each cycle consists of two meetings. The subjects of this research were students in class VII.2 of SMP Negeri 10 Palembang, totaling 27 students consisting of 14 boys and 13 girls. Based on the results of classroom action research which has been carried out in two cycles, the aim is to improve the learning outcomes of class VII.2 students at SMP Negeri 10 Palembang using the problem based learning model. Based on the pre-action results, it shows that as many as 12 students or 44.44% completed their studies with an average score of 68.22. The test results in cycle I increased to 14 students or 51.85% who were declared complete in learning with the average score increasing to 73.70. From the results of the second cycle test, meeting 1, data was obtained with an average value of 80.15 and at meeting 2, data was obtained with an average value of 81.78. The test results in cycle II increased to 24 students or 88.88% who were declared complete in learning with the average score increasing to 81.44.